1997
DOI: 10.1046/j.1365-3024.1997.d01-226.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunological cross reactivity between Schistosoma mansoni and cholera toxin

Abstract: Intranasal administration of schistosome antigens in combination with appropriate adjuvant may be an effective route for immunization against schistosomes, since the lungs represent an important site of elimination of schistosomulae. Our previous studies have shown that in mice intranasal administration of cholera toxin (CT) before infection with Schistosoma mansoni results in an enhancement of the worm burden in comparison to nontreated infected animals. In the present study, it was shown that mice treated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The widespread occurrence of cross-reactive antibodies to P. falciparum and S. mansoni infections has not, to our knowledge, been reported elsewhere, although Moser et al [37] showed that patients with malaria were able to recognize the S. mansoni heat shock protein 70 and although both malaria and schistosomiasis are known to induce antibodies to cross-reactive epitopes present on other pathogens. For example, antibodies from S. mansoni-infected patients who did not have fascioliasis recognized Fasciola hepatica antigens [38], whereas antibodies from individuals infected with S. mansoni who did not have cholera recognized cholera toxin [39]. Similar observations were described for reactions in serum from S. mansoni-infected patients to Trichinella spiralis [40], hookworm, and Ascaris lumbricoides [41].…”
Section: Notementioning
confidence: 66%
“…The widespread occurrence of cross-reactive antibodies to P. falciparum and S. mansoni infections has not, to our knowledge, been reported elsewhere, although Moser et al [37] showed that patients with malaria were able to recognize the S. mansoni heat shock protein 70 and although both malaria and schistosomiasis are known to induce antibodies to cross-reactive epitopes present on other pathogens. For example, antibodies from S. mansoni-infected patients who did not have fascioliasis recognized Fasciola hepatica antigens [38], whereas antibodies from individuals infected with S. mansoni who did not have cholera recognized cholera toxin [39]. Similar observations were described for reactions in serum from S. mansoni-infected patients to Trichinella spiralis [40], hookworm, and Ascaris lumbricoides [41].…”
Section: Notementioning
confidence: 66%
“…These results suggest that peptides LS1.1 and LS1.2 may represent sequences that are similar to those in the putative P. berghei LSA-1 or even perhaps in some other P. berghei antigens. However, how these peptides with no apparent sequence homology can cross-react both at the T-cell and B-cell levels is well established (1,21,39).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, sera from mice and humans infected with S. mansoni recognized a 22‐kDa antigen of CT by Western blot. These findings are indicative of an immunological cross‐reactivity between S. mansoni and CT [13].…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, we found that intranasal administration of CT in mice followed by challenge infection with S. mansoni cercariae induced a significant increase in worm burden when compared with PBS‐treated control mice [12]. It was also shown that administration of CT to uninfected mice induced high levels of schistosome‐reactive IgM antibodies [13], recognizing a 22‐kDa antigen on blots of separated soluble adult worm antigen (SWAP). Furthermore, sera from mice and humans infected with S. mansoni recognized a 22‐kDa antigen of CT by Western blot.…”
Section: Introductionmentioning
confidence: 99%